Refleksi Nilai-Nilai Pancasila dalam Gerakan Sosial Duta Kayu Agung: Antara Keadilan, Kemanusiaan, dan Persatuan - Lidiawati, Citra; Damayanti, Hikma; Mazid, Sukron (Universitas Muhammadiyah Ponorogo, 2026)
Social movements often present ethical dilemmas in assessing the legitimacy of their actions, whether the resistance that emerges is a form of social banditry or actually represents a struggle for justice. This article analyzes the dynamics of the Duta Kayuagung social movement using the theoreticalframework of social banditry proposed by Hobsbawm, Rawls's theory of justice, and the theory of civil resistance. The selection of these three theoretical perspectives is intended to broaden the analytical horizon, while also demonstrating the connection between local resistance practices and auniversal normative framework. This research uses a qualitative literature study method by examining various academic sources, historical documents,and relevant social records regarding Duta Kayuagung. The results show that the Duta Kayuagung movement cannot be simply reduced to social banditry as Hobsbawm's classic definition, because their actions have a strong moral basis and are grounded in the spirit of distributive justice and siding with oppressed communities. From Rawls's perspective, their actions can be understood as an effort to uphold the principles of fairness and equal opportunity, while within the framework of civil resistance, this movement reflects a form of ethical resistance against structural injustice. Furthermore, when analyzed through reflection on the values of Pancasila, particularly the second principle on just and civilized humanity, the third principle on Indonesian unity, and the fifth principle on social justice, the Kayuagung Ambassador movement is more appropriately positioned as afighter for justice rooted in the nation's noble values. This finding confirms that Pancasila is not only the philosophical foundation of the state, but can also function as an ethical and normative framework in understanding social movements in both historical and contemporary contexts. Thus, this study not only provides a conceptual mapping of the Kayuagung Ambassador movement but also strengthens the relevance of Pancasila as an analytical foundation in assessing the dynamics of social movements in Indonesia, so that they remain contextual in facing the challenges of globalization and social transformation.